Political gender stereotypes in a list- PR system with a high share of women MPs : competent men versus leftist women? - Devroe, Robin; Wauters, Bram (2018)
On the basis of a candidate$1 (Bs sex, voters ascribe particular personality traits, capacities, and opinions to candidates (often to the detriment of women), which are referred to as political gender stereotypes. The prevalence of political gender stereotypes has almost exclusively been investigated in the United States. As the presence of these stereotypes is highly dependent on contextual factors, we switch the context and investigate whether they are also present in a List-Proportional Representation (PR) system with a high share of women in parliament spread over different parties. The results of our experimental study, conducted in Flanders (Belgium), provide evidence for the existence of stereotypical patterns. The differences in perceived issue competence are, however, rather small and not always unequivocal, but larger differences were found in terms of ideological position. This leads us to conclude that misperceptions about women$1 (Bs ideological orientation might be persistent and difficult to overcome. Moreover, our results demonstrate that the argument that female politicians are perceived as more leftist because they disproportionately belong to leftist parties does not hold, as female politicians are rather equally spread over the different parties in Belgium. - Reproduced.s
Keywords: Political representation